Spanish for the rest of us - Harvey, William C. (New York McGraw Hill, 2021)
"If you're one of the rest of us, this practical guide is for you! You will learn Spanish not by memorizing boring grammar rules, but by focusing on everyday, practical language. Author William Harvey emphasizes the most-often-used Spanish words and phrases, and reveals numerous language-learning tips that provide shortcuts to effective communication. And this lively, informal program is supported by audio recordings (online and via mobile app) to give you complete confidence in your Spanish pronunciation.
Whether you need to communicate with Spanish speakers at work, in social situations, or on your travels, Spanish for the Rest of Us is the quick and easy way to understand and make yourself understood in Spanish!" --Back cover.
"Everyday Spanish without the rules" --Cover.
"Extensive audio recordings (requiring internet connection) and vocabulary flashcards are available to support your study of this book. Go to www.mhlanguagelab.com to access the online version of this application, or to locate links to the free mobile app for iOS and Android devices. More details about the features of the app appear on the inside front and back covers" --Verso t.p.
Keywords: Spanish language -- Conversation and phrase. -- English; Spanish language -- Textbooks for foreign speakers. -- English; Spanish language -- Grammar; Spanish language -- Self-instruction.